Unruly Narrative Private Property, Self-Making, and Toni Morrison's ›A Mercy‹ - Spatzek, Samira (American Frictions, 2022)
This study deals with the formative powers of modern liberal ideas of private property. The liberal subject emerged with the formations of European liberalism, Atlantic slavery, and settler colonial expansion in the New World. Toni Morrison's A Mercy is thus identified as a key literary text that generates a fundamental critique of the connections between self-making and private property at its 17th-century scene.